Social History of Islamic Banking and First Example: Bank-I Awqāf - Akgunduz, Ahmed (Journal of Islamic and Social Studies, 2024)
The cash waqf was a special category of Islamic endowment and played an important role in the economic/financial history of the Ottoman Empire. As such, it can be considered an important Islamic financial institution that facilitated the flow of funds from those who could save to those who needed capital, i.e. primarily entrepreneurs as well as the general public. This institution is also considered one of the most important Ottoman contributions to Islamic civilisations. Ottoman scholars have been discussing Islamic banking since Suleiman the Magnificent (1574). Islamic banking was known in the Ottoman state as Mu'amalah al-Shar'iyyah, which we can simply call murâbahah. The Ottoman state established the "Awariḍ Akcasi Sandiklari", which means "The Box of Waqf Money". Ottoman scholars preferred "Mudaraba" and murâbahah or qarḍ. This practice continued with the establishment of the Awqaf Bank in 1914. On 1914, the Ottoman Ministry of Awqaf decided to establish the first Islamic bank, Bank-i Ewqaf, with its central branch in Istanbul and possible new branches in all provinces. The bank's system was entirely Mu'amalah al-Shar'iyyah or simply Murâbahah. This bank had the right to issue bonds, certificates, transfer money, etc.